До побудови моделі рівноваги економічної макросистеми - Pankratova, N. D.; Shelest, A. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2013)
The issues related to economic equilibrium and macroeconomic stability are considered. The main purpose of this work is to build a general equilibrium model, which allows to evaluate the stability of the national economy on the basis of key macroeconomic indicators. The novelty of the work is in developing a formal criterion of stability of the economic system, which allows to estimate this option and, accordingly, allows to make a conclusion about current situation in the economy. As an example, economic system of Ukraine was selected. The results of numerical experiments confirm the erratic nature of the development of the national economy, which suggests the possibility of practical application of the model to study the macroeconomic stability.